Os agricultores familiares e suas estratégias de gestão: o PRONAF B no território Açu-Mossoró - Solano, Sarah Laurentina Tomaz (Universidade Federal Rural do Semi-Árido, 2017)
This current study brings as main topic the family agriculture and management strategies used by family farmers. Family agriculture is responsible for production of 70% of foods consumed by brazilians, 64% of occupations in rural areas and 10% of brazilian GDP, contradicting scholars such as Kautsky, who predicted the family farmer extinction before the accelerated growth of agribusiness and these smallholders are still surviving in the midst of a dynamic and complex market. Over the years, many public policies were developed aiming to promote the growth of agricultural segment, but such measures were predominantly benefiting great enterprises in rural areas. After years of struggle, in 1996 was created the National Program for Sustainable Family Agriculture (PRONAF in Portuguese), which emerged aiming to promote the development for these small rural enterprises, as well as providing improvements in quality of life of these family farmers who contribute so much to the food production. Among credit lines, this work standeth in PRONAF B, a microcredit line directed to low incomes family farmers, which allows access to low values credit offering tax compliance discounts and reaching up to 25% of the value taken. However, even with so many incentives for tax compliance, PRONAF B had high elinquency rates, which led to the creation of the Oriented Rural Microcredit Program (AGROAMIGO), which provides credit to family farmers benefiting from PRONAF B, with monitoring of credit agents assisting since the project preparation until the process is complete with the transaction settlement. In this context of lending policies directed to family farming, this research had as main goal analyzing how family farmers in Assu-Mossoro are using resources provided by PRONAF B from 2009 to 2014. In order to meet the proposed goal, it was applied a field research with qualitative, exploratory and descriptive approaches, adopting as data collection instrument an interview structured consisting of 18 questions. The study site was conducted in Assu- Mossoro territory composed of 14 counties, where were interviewed 5 family farmers benefited by AGROAMIGO within the period of the study. From the collected data, it was concluded that the family farmers benefited by AGROAMIGO in the study site do not use, in their great majority, management tools in their rural businesses, possibly due to the low level of schooling found among interviewees. This could be an indicator of a need for a more effective presence on the part of ATER in order to enable these farmers to undertake a management of their businesses so that obtain a sustainable development and improving the quality of life of those involved. It is possible to know more from the interviews conducted, such as the perception on the part of the beneficiaries about benefits offered by PRONAF. However, it is a latent need that still exists for the program improvement in order to achieve the goals proposed
Family farmers and their management strategies: PRONAF B in Açu-Mossoró (RN) territory
Keywords: Agricultura familiar; PRONAF; Desenvolvimento territorial; Family farming; PRONAF; Territorial development; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE